The significance of groundwater contributions to New Zealand rivers - Moore, Catherine; Oluwunmi, Paul; Hemmings, Brioch; Cameron, Stewart; Yang, Jing; Taves, Mike; Rajanayaka, Channa; Woodward, Simon J. R.; Moreau, Magali (Frontiers in Water, 2025)
Groundwater and surface water are highly interconnected systems, with the connections varying spatially, temporally and by catchment. Representing this connectivity is of key importance for future effective water management, and to address the global decline of surface water flows. Previous studies have used baseflow separation methods to quantify the groundwater contribution to surface flow volumes. However, few studies have analysed the different dynamics of deep and shallower groundwater contributions to surface water flow rates across the flow regime and attempted to quantify this changing contribution. We analysed the distribution of fast (near-surface event flow), medium (seasonal shallow groundwater discharge) and slow (deeper groundwater) pathways into surface water flows for a case study involving 58 river water quality and flow monitoring sites across New Zealand. This involved a novel application of the chemistry assisted baseflow separation method (BACH). We found that shallow and deep groundwater pathways were the most significant contributor (>80% of the daily flow rate) to river flow at most sites at the 75th flow percentile, and for many sites even at the 95th flow percentile. These findings emphasise the need to better integrate groundwater into surface water management strategies, particularly as droughts intensify, floods become more frequent and severe, and legacy nutrient input increases under changing climate and land-use.